Exploring New Cultures and Their Implications for Gen-Z Religious Life: A Sociological and Anthropological Perspective in the Contemporary Era - Soleh, Muhammad; Kuncoro, Irfan; Ma’ruf, Chasan (STAI Publisistik Thawalib Jakarta, 2023)
Online media shapes the religious hybridity of Gen-Z, influencing attitudes towards pluralism, spirituality, and challenging conservative religious traditions. This study aims to explore the new culture and its implications for Gen-Z’s religious practices in the context of contemporary society. The research uses a qualitative literature study, with data collected through content analysis of articles. The findings show that Gen-Z is influenced by technological advancements and globalization, which provide them with broad access to information through the internet and social media. They tend to be more inclusive and open to various religious traditions, often combining elements from different religions or creating personal spirituality. Technology also allows them to build digital identities and engage in social activism. Social media plays a significant role in shaping their religious views and practices, though it also presents challenges, such as dilemmas between traditional religious values and modern cultural pressures. Gen-Z requires support to navigate these conflicts and challenges. Conclusion: Gen-Z is influenced by technology and globalization, creating an inclusive and personal religious culture by combining elements of religion and spirituality, accessed through social media.